PENGARUH MOTIVASI DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA PENDAMPING PROGRAM KELUARGA HARAPAN KEMENTRIAN SOSIAL KABUPATEN LAMPUNG TIMUR - Dwi Wijayanto (Universitas Bandar Lampung (UBL), 2016)
ABSTRACT Achievement of organizational goals is influenced by its employees. Employees should be given the motivation to work more diligently in order to produce a performance that is consistent with the objectives of the organization. Besides motivation, human resources plays a very important in an organization. For that I am keen to take the title Motivation Influence of Human Resources and Quality Companion Program Performance Against Family Hope Ministry of Social Affairs in East Lampung regency.This study aims to identify and explain 1) Effect of Motivation on Performance Companion Social Ministry of the Family Hope Program In East Lampung district